Step
*
2
1
of Lemma
fun-path-fixedpoint
1. T : Type
2. f : T ⟶ T
3. u : T
4. v : T List
5. ∀[x,y,z:T].  (y = z ∈ T) supposing (((f y) = y ∈ T) and (y ∈ v) and z=f*(x) via v)
6. x : T
7. y : T
8. z : T
9. z=f*(x) via [u / v]
10. (y ∈ v)
11. (f y) = y ∈ T
⊢ y = z ∈ T
BY
{ DVar `v' }
1
1. T : Type
2. f : T ⟶ T
3. u : T
4. ∀[x,y,z:T].  (y = z ∈ T) supposing (((f y) = y ∈ T) and (y ∈ []) and z=f*(x) via [])
5. x : T
6. y : T
7. z : T
8. z=f*(x) via [u]
9. (y ∈ [])
10. (f y) = y ∈ T
⊢ y = z ∈ T
2
1. T : Type
2. f : T ⟶ T
3. u : T
4. u1 : T
5. v : T List
6. ∀[x,y,z:T].  (y = z ∈ T) supposing (((f y) = y ∈ T) and (y ∈ [u1 / v]) and z=f*(x) via [u1 / v])
7. x : T
8. y : T
9. z : T
10. z=f*(x) via [u; [u1 / v]]
11. (y ∈ [u1 / v])
12. (f y) = y ∈ T
⊢ y = z ∈ T
Latex:
Latex:
1.  T  :  Type
2.  f  :  T  {}\mrightarrow{}  T
3.  u  :  T
4.  v  :  T  List
5.  \mforall{}[x,y,z:T].    (y  =  z)  supposing  (((f  y)  =  y)  and  (y  \mmember{}  v)  and  z=f*(x)  via  v)
6.  x  :  T
7.  y  :  T
8.  z  :  T
9.  z=f*(x)  via  [u  /  v]
10.  (y  \mmember{}  v)
11.  (f  y)  =  y
\mvdash{}  y  =  z
By
Latex:
DVar  `v'
Home
Index